The great ideas of philosophy - Robinson, Daniel N.; Aigret, Jaimée M.; Leven,Jon; Dooley,Tom (Great courses, 1997)
Sixty lectures by Daniel N. Robinson tracing the abiding issues of philosophy across the centurie.